Abordaje lumbar intermuscualr de Wilse en patología no discal - Mezzadri, Juan José; Rivadeneira, Conrado; Campero, Alvaro; Basso, Armando (Revista Argentina de Neurocirugía, 2021)
We analyse the results obtained with the Wiltse lumbar intermuscular approach in three cases with non-discal pathology which compromised the foraminal and extraforaminal areas. Case 1 (female/ 59 years) with a history of primary skin lymphoma, sufferedfrom L5 radicular pain caused by an L5-S I hyperintense tissue in MRI. Biopsy was not specific. Case 2 (female/ 33 years) suffered from L5 radicular pain caused by a left megatransverse L5 process which was completely resected. Case 3 (female/ 23 years) with a history of abdominal surgery for a congenital tumour, the MRI showed an hyperintense tissue that invaded extensively de spinal canal through T12-L4 foramina. Biopsy informed ganglioneuroma. After surgery radia llar pain gave up in cases 1 & 2. After 72 hours patients were discharged without complications. This was a safe and dírect approach that was greatly assisted by microsurgical techniques.